COLLABORATION BETWEEN HOSPITALS AND THE CIVIL REGISTRATION OFFICE IN PROVIDING CIVIL ADMINISTRATION SERVICES: (CASE STUDY AT LA MAPPAPENNING REGIONAL PUBLIC HOSPITAL, SOUTH SULAWESI PROVINCE) - Andi Widyawaty; Deasy Mauliana; A. Selvi Kartini Wonsu; Herawati Herawati; Fhirawati Fhirawati (Jurnal Administrasi Negara, 2025)
This research aims to analyze the effectiveness of public service collaboration in the fields of health and civil administration. The study focuses on a case involving children born at the La Mappapenning Regional General Hospital (RSUD) in Bone Regency, South Sulawesi Province, Indonesia. The collaboration between the RSUD and the Civil Registration Office (Dukcapil) of Bone Regency is designed to facilitate the direct issuance of civil documents (Birth Certificates, Family Cards, and Child Identity Cards) at the hospital, eliminating the need for a separate visit to the Dukcapil office. This study employs a descriptive qualitative approach using Huxham's theory of Collaborative Advantage, which includes four dimensions: managing goals, managing trust, managing culture, and managing leadership. Data were collected through interviews, observations, and documentation with fifteen informants. The results indicate that while the collaboration is effective due to the convenience and efficiency it provides, its implementation still faces challenges. Those challenges are differences in goals, an imbalance of roles, limitations of integrated information systems, and a lack of clarity in the leadership structure for decision-making. By adaptively managing the dynamics of trust, organizational culture, and the active participation of leaders from both institutions, this collaboration has the potential to become an innovative model for inclusive and effective public service. This research contributes theoretically to the practice of collaborative governance and offers practical recommendations for optimizing cross-sector partnerships in hospital-based public services.